Studi kasus Dampak Pembangunan Infrastruktur terhadap Kehidupan Masyarakat Melalui Kacamata Sosiologi: Tanda Tanya Pembangunan Infrastruktur Jalur Kereta Api trans-Sulawesi - Ignatius Aji Dwiatmaja; Muhammad Imam Alfikri; Irfan Khairan Ali (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study aims to explore the impact of the trans-Sulawesi railway infrastructure development intervention on people's lives. With a qualitative case study approach, this research will focus on three aspects: economic, social, and environmental, to understand the dynamics of change and community response. In the economic aspect, changes in livelihood, income, and employment opportunities will be examined. Socially, the influence of infrastructure on interaction, cohesion, culture, and local wisdom will be explored. The environment will highlight issues of spatial planning, land use, habitat destruction, and biodiversity threats. The findings are expected to provide a comprehensive understanding of community dynamics in responding to interventions, as well as input for policymakers to design interventions that are more responsive to community needs and aspirations.